Implementasi Knowledge Sharing Behavior Dan Disiplin Kerja Untuk Peningkatan Produktivitas Kerja Karyawan - Anita Saputri; Idris, Idris; Wahyuni Adda, Harnida; Murad, Moh. Ali (JURNAL MANAJEMEN MOTIVASI, 2026)
Employee productivity is essential for achieving organizational goals, especially in the automotive industry, which faces intense competition and rapid technological change. This study analyzes the effects of knowledge sharing behavior and work discipline on employee productivity at PT. Kalla Toyota Martadinata. Using a quantitative survey, data was collected from all 48 employees through saturated sampling and analyzed with multiple linear regression using SPSS 31. The results show that both variables simultaneously and significantly affect productivity. Work discipline has the dominant positive effect, while knowledge sharing behavior contributes significantly but more modestly. The model explains 69.9% productivity variation. Keywords: Knowledge Sharing Behavior; Work Discipline; Work Productivity